Enterprises, incentives and networks: the formative years of the electrical network in Portugal, 1920–1947 - Madureira, Nuno Luis (Business History, 2007)
Path-dependence, the formation of technological irreversibilities and ownership patterns, have recently been salient aspects in the study of historical networks. This article analyses the formative years of public utilities in a period where the advantages of co-ordination, interconnection or integration between enterprises was still incipient. The purpose is to understand what happens when the competition to expand the physical extensions of nodes and links is suddenly blocked, and the enterprises can only compete to increase supply. The theme is thus of network enterprises operating without some of the standard incentives to economies of scale. The allocational and distributional consequences of this particular situation are exposed through an examination of the case study of Portuguese electrification in the first half of the twentieth century